Pengaruh Service Quality dan Product Quality terhadap Loyalitas Pelanggan Kopi Kenangan: (Studi pada Pelanggan Kopi Kenangan di Kota Binjai) (Jurnal Manajemen Kreatif dan Inovasi, 2025)
The growth of coffee consumption in Indonesia presents challenges for Kopi Kenangan in maintaining customer loyalty amidst the increasingly competitive beverage industry. This study aims to analyze the influence of service quality and product quality on customer loyalty at Kopi Kenangan, Ruko Sultan Hasanuddin, Binjai City, both partially and simultaneously. The research employed an associative quantitative approach with 96 respondents selected through incidental sampling. The research instrument was a questionnaire designed with indicators representing the dimensions of service quality and product quality. The data were analyzed using multiple linear regression, partial tests (t-test), simultaneous tests (F-test), and determination tests to identify the contribution of independent variables to the dependent variable. The findings reveal that service quality and product quality have a positive and significant effect on customer loyalty. For service quality, the tangible indicators, such as store comfort and adequate facilities, are dominant factors that enhance customer satisfaction. Meanwhile, for product quality, the performance indicators, including coffee taste and product consistency, play a crucial role in fostering customer loyalty. Loyalty is reflected in repeated purchases, brand commitment, and resistance to competitor products. Nevertheless, the study also indicates that menu variation has not fully encouraged repeat purchases, highlighting the need for greater product innovation. Recommendations include improving store environment comfort, providing staff training for optimal service delivery, ensuring taste and quality consistency, developing product design innovation, and implementing experience-based marketing strategies along with loyalty programs. These efforts are expected to strengthen emotional bonds and enhance Kopi Kenangan’s competitiveness in the long term.